Lançamentos de foguetes como uma ferramenta pedagógica para o ensino de física - Oliveira, Fernando Sousa de (2019)
The present work aimed at the realization of a series of practical experimental classes for the construction, production and launch of PET rockets, with the purpose of awakening in the scientific disciplines of interest and providing a more friendly relationship with a discipline of. The project was carried out with the second year of High School in Instituto Federal de Mato Grosso, Sorriso/MT, in 2015. The study of water rockets with PET bottles allows exploring, with diverse approaches - with emphasis on experimentation - curricular subjects of the discipline of Mechanics, such as movement in the plane, applications of the Laws of Newton, center of mass, as well as to provide multidisciplinary opportunities with the mathematics, and chemistry by studying, for example, rocket geometry and fuel, respectively. The educational product generated consists of the PET Bottle Rocket Experimentation Guide, which involves 9 (nine) experimental classes that deal from the construction of the rocket, its launch to the analysis of possible problems and failures, and the analysis of its efficiency. In order to motivate the students to participate in the activities, we emphasized the competitive nature of the launches, encouraging the formation of teams and creating a mini-championship in the class. As a result of our work, we mentioned the excellent opportunity to discuss, in an integrated way, several mechanics concepts and quantities that, when taught exclusively in the classroom, did not seem to arouse students' interest. Yet, we highlight the importance of physics for technological applications - although it seems an obvious relationship, often this association is not easily first seen by students. In the student part, we highlight the experience with the experimental classes and the motivation provided by the experimentation that contributed positively to the dynamics of the theoretical classes.